COPO: a metadata platform for brokering FAIR data in the life sciences - Shaw, F; Etuk, A; Minotto, A; Gonzalez-Beltran, A; Johnson, D; Rocca-Serra, P; Laporte, M-A; Arnaud, E; Devare, M; Kersey, P; Sansone, S-A; Davey, RP (F1000 Research Ltd, 2020)
Scientific innovation is increasingly reliant on data and computational resources. Much of today’s life science research involves generating, processing, and reusing heterogeneous datasets that are growing exponentially in size. Demand for technical experts (data scientists and bioinformaticians) to process these data is at an all-time high, but these are not typically trained in good data management practices. That said, we have come a long way in the last decade, with funders, publishers, and researchers themselves making the case for open, interoperable data as a key component of an open science philosophy. In response, recognition of the FAIR Principles (that data should be Findable, Accessible, Interoperable and Reusable) has become commonplace. However, both technical and cultural challenges for the implementation of these principles still exist when storing, managing, analysing and disseminating both legacy and new data.